Coniophoropsis bambusicola sp. nov. (Coniophoraceae, Basidiomycota) from southern Vietnam - Zhao, Ya-Nan; Liu, Shi-Liang; Nakasone, Karen K.; He, Shuang-Hui (Phytotaxa, 2018)
Coniophoropsis bambusicola sp. nov. is described and illustrated from southern Vietnam based on morphological and molecular evidence. It is the second species in the genus, and differs from the type, C. obscura, by having much smaller basidiospores measuring 5.5–7 × 4–5 µm and growing on the culms of dead bamboo. The phylogenetic analyses based on a combined dataset of nuc rDNA ITS1-5.8S-ITS2 (ITS) and nuc 28S rDNA (28S) sequences of Boletales show that Coniophoropsis bambusicola is closely related to Coniophora.